أثر التضخم على البطالة في الجزائر – دراسة قياسية باستخدام نموذج الإنحدار الخطي البسيط - مجطوح فضيلة; ياسف حسيبة (جامعة الوادي University of Eloued, 2024)
هدف هذه الدراسة إلى قياس أثر التضخم على البطالة في الجزائر في الفترة الممتدة ما بين (1989 – 2017)، تم التطرق إلى المفاهيم الأساسية المعنية بالموضوع و إستعراض تطور التضخم وتطور البطالة وكذا صياغة وبناء النموذج القياسي للعلاقة بين متغيرات الدراسة، وذلك بالإعتماد على تقدير العلاقة وفق نموذج الإنحدار الخطي البسيط، كشفت النتائج المتحصل عليها على وجود علاقة طردية ضعيفة بين التضخم والبطالة في الجزائر خلال فترة الدراسة، وأن الزيادة في التضخم بقيمة 1 مليون دولار سيزيد البطالة بقيمة 0,353. This study aims to measure the impact of inflation on unemployment in Algeria during the period between (1989-2017), the basic concepts concerned with the subject were addressed and a review of the development of inflation and the development of unemployment as well as the formulation and construction of the standard model for the relationship between the variables of the study, based on the estimation of the relationship According to the simple linear regression model, the obtained results revealed that there is a weak direct relationship between inflation and unemployment in Algeria during the study period, and that an increase in inflation by $1 million will increase unemployment by a value of 0.353.
The effect of inflation on unemployment in Algeria - an econometric study using the simple linear regression model
Keywords: تضخم; بطالة; ركود تضخمي; الجزائر; SPSS; inflation; unemployment; stagflation; Algeria